PERAN OLAHRAGA DALAM PEMBENTUKAN KARAKTER ISLAMI SISWA DI SDIT AD- DA’WAH - M. Ghazwa I. F.; Desty Endrawati Subroto; Muhammad Juang Maghribi; Dafa Hakim; Khofif fauzi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Sport has an important role in character formation, especially in the context of Islamic values. This research aims to explore how sports activities can facilitate character development such as discipline, cooperation and honesty among Muslim individuals. The aim of the research is to determine the important role of sport in forming the Islamic character of students, especially SDIT AD-DA'WAH students. The method used in this research is a qualitative approach with in-depth interviews with coaches, athletes and parents, as well as observational analysis of various sports activities in the Muslim community. The results of this research show that sport has an important role as an instrument in forming students' Islamic character, especially in the SDIT AD-DA'WAH environment. The values contained in sports include an attitude of responsibility, mutual respect for each other, a love of worship, having a high level of perseverance and a spirit of cooperation, being honest in your behavior, having high integrity and many other positive attitudes. This shows that sport has a very important role in the process of forming students' Islamic character. Sport is also a driving tool or instrument which has the power to change students' mindsets and thinking patterns in order to become human beings with noble character